A Predictive Test of Voters' Economic Benchmarking: The 2013 German Bundestag Election. Issue 1 (2nd January 2016) - Kayser, Mark Andreas; Leininger, Arndt
Abstract : Do voters judge their national economy relative to economic performance abroad? In 2013 we took advantage of the German Bundestag election to test this hypothesis predictively. Nearly two months prior to the election, we published an election forecast relying on a theory-driven empirical model of election outcomes that draws on previous election outcomes; characteristics of the government and of voters; and, most originally, the relative economic performance of Germany ('benchmarked' growth) in comparison to the three other most important economies in Europe – France, the UK and Italy. Our forecast put the outgoing coalition government of CDU/CSU and FDP at 47.05 per cent of the popular vote deviating from the actual outcome of 46.3 by 0.75 points. This makes our forecast one of the most accurate in this election cycle. Despite one-and-a-half months of lead time, our forecast performed on par or slightly better than the last poll results issued only two days before the election.